2014
DOI: 10.1007/s00418-014-1295-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolabeling of gamma-glutamyl transferase 5 in normal human tissues reveals that expression and localization differ from gamma-glutamyl transferase 1

Abstract: Gamma-glutamyl transferase (GGT5) was discovered due to its ability to convert leukotriene C4 (LTC4, a glutathione S-conjugate) to LTD4 and may have an important role in the immune system. However, it was not known which cells express the enzyme in humans. We have developed a sensitive and specific antibody that can be used to detect human GGT5 on western blots and in fixed tissue sections. We localized GGT5 expression in normal human tissues. We observed GGT5 expressed by macrophages present in many tissues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…At the same time, LTD 4 was formed in long-term incubations of MM6 cells, in agreement with these cells (Fig. 7), as human macrophages (19), expressing GGT5. However, in previous experiments with lung tissue, induced formation of CysLT including LTD 4 was quick (10-15 min) [see (49)], suggesting involvement of GGT1.…”
Section: Formation Of Cyslt In Coincubations Of Pbecs With Mm6 Cellssupporting
confidence: 83%
See 1 more Smart Citation
“…At the same time, LTD 4 was formed in long-term incubations of MM6 cells, in agreement with these cells (Fig. 7), as human macrophages (19), expressing GGT5. However, in previous experiments with lung tissue, induced formation of CysLT including LTD 4 was quick (10-15 min) [see (49)], suggesting involvement of GGT1.…”
Section: Formation Of Cyslt In Coincubations Of Pbecs With Mm6 Cellssupporting
confidence: 83%
“…However, human GGT5 was less efficient compared with human GGT1 regarding formation of LTD 4 in vitro (9). Recently, GGT5 was found in macrophages present in human tissues, most abundant in the lung (19).…”
Section: Timeline Of Cell Culture and Coculturementioning
confidence: 95%
“…The gGT1 promoter has been used by several groups to generate proximal tubule-specific deletions of target genes (Iwano et al, 2002;Chen et al, 2012;Inoue et al, 2012;Tiwari et al, 2013;Han et al, 2016;Zhou et al, 2018). Although gGT1 can also be expressed in hepatocytes, it is expressed in much higher levels in proximal tubule cells (Hanigan et al, 2015), and gGT-Cre mice primarily express Cre in the kidney (Iwano et al, 2002). Further work showed that gGT-Cre deletes floxed genes in only proximal tubule cells (Chen et al, 2012;Inoue et al, 2012;Tiwari et al, 2013;Han et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Different letters denote P , 0.05, Two-way analysis of variance (ANOVA) with Fisher's least significant difference (LSD) test. types (Hanigan et al, 2015), particularly in pathologic states such as polycystic kidney disease (Starremans et al, 2008) and epithelial-mesenchymal transition (Inoue et al, 2010), the gGT-Cre mouse generates a proximal tubule-specific deletion of floxed genes without any Cre-dependent effects on renal function.…”
Section: Discussionmentioning
confidence: 99%
“…But GGT5 gene knockout mice were unable to metabolize LTC4 , resulting in diminished potential of neutrophils infiltrating into the peritoneum. The expression and function of GGT5 in human are rarely reported [ 22 ]. PTGS2 (also known as COX-2 ) could promote carcinogenesis and metastasis of multiple types of tumors.…”
Section: Discussionmentioning
confidence: 99%